Stover quality traits for improvement of dual-purpose sorghum - Ramkrishna, R.C.; Khan, A.A.; Prasad, Kodukula V.S.V.; Ravi, D.; Reddy, B.V.S.; Rego, T.; Blümmel, Michael (2010)
Twenty four sorghum stovers were investigated with sheep for organic matter digestibility (OMD) and intake (OMI), and for digestible organic matter intake (DOMI) and for relations between laboratory fodder quality traits and these in vivo measurements. Statistically highly significant and nutritionally important differences were found between the stover with OMD differing by 15 percentage units and OMI and DOMI varying 1.6 and 2 times, respectively. For each of the in vivo measurements, chemical (NDF, ADF, ADL) and in vitro (in vitro digestibility, metabolisable energy content) traits were identified which accounted for at least 50% of the variation in the respective traits. Using multiple regression procedures and stringent cross-validation (“blind-predictions”) procedures OMD, OMI and DOMI could be predicted with R2 for comparing observed and predicted values of 0.36, 0.65 and 0.75, respectively. The reported research showed selection for dual purpose sorghum cultivars is promising, and identified and validated simple laboratory traits that can be used for such phenotyping.